SÍZÍQLÍ EMES OPTIKANÍŃ EKINShI GARMONIKALÍQ GENERACIYASÍNDA ÚSh TOLQÍNLÍ ÓZ ARA TÁSIRLESIWLER - Akimova, J.O. (SCIENCE and SOCIETY, 2025)
In this article, there is no opportunity to analyse the influence of linear and nonlinear absorption of radiation on the processes under consideration. Nevertheless, it was established how complex it is to calculate and experimentally investigate the nonlinear wave interaction of the main factors in the mentioned complex medium.